A Centrally Driven Place-Based Economic Development Strategy: A Local Perspective of Thailand’s Eastern Economic Corridor - Kamnuansilpa, Peerasit; Timofeev, Andrey; Lowatcharin, Grichawat; Laochankham, Sirisak (International Journal of Membrane Science and Technology, 2023)
We contrast place-based economic development strategies (PBEDS) in Thailand and in economically advanced countries. Through government initiatives, PBEDS focuses on improving economically underdeveloped areas’ economic conditions. Thailand’s PBEDS began in 1959 to develop the impoverished Northeast region, focusing on agricultural improvements. Since 1970, infrastructure and industrial development zones have been the main strategies to attract foreign investment for export-oriented growth. In economically advanced countries, the primary purpose of PBEDS is to reduce regional economic disparity. However, as they are implemented in Thailand, they increase regional inequality as development is concentrated in and around Bangkok. Thailand’s latest PBEDS is the Eastern Economic Corridor (EEC) project in three eastern provinces. The national government oversaw the EEC and granted the EEC Office special powers to streamline investment approvals, although local governments have no formal role. We contrast Thailand’s top-down PBEDS with approaches in other countries that emphasize local decision-making and leveraging regional assets. Thailand’s policies focus on national growth, while international evidence suggests that locally-led PBEDS more effectively address regional disparities and increase national output. Thailand should empower local governments, coordinate with them, and invest in poorer regions. At the same time, the EEC may promote growth, but its centralized approach risks misaligning with local needs. A balanced strategy accounting for local contexts could better lift Thailand economically.